A Combined Epithelial Odontogenic Tumor? A 7-Year Follow-Up Case - Garcia Rosa, Ana Claudia; Soares, Andresa Borges; Furuse, Cristiane; Rodrigues Lima, Sandro Regis; Araujo, Vera Cavalcanti de; Passador-Santos, Fabricio (Springer, 2017)
Adenomatoid odontogenic tumor (AOT) is a benign epithelial odontogenic tumor characterized by slow and progressive growth. When central lesions are associated with an unerupted permanent tooth, they are also known as the follicular type. Histological variants of AOT may complicate diagnosis with possible adverse effects on treatment and prognosis. The aim of this study is to report a case of a follicular AOT with extensive calcifying epithelial odontogenic tumor (CEOT)-like histopathological areas in the anterior region of the mandible that was treated by enucleation. The teeth displaced by the tumor were repositioned with orthodontic treatment, and after 7 years of follow-up, the bone trabeculae were normal with no evidence of recurrence. The clinical, radiographic and histopathologic aspects of these tumors are discussed and the debate surrounding whether these cases are true combined lesions or histologic variants of the primary tumor is raised.
Keywords: Adenomatoid odontogenic tumor; Calcifying epithelial odontogenic tumor; Congo red staining; Odontogenic epithelium; Odontogenic tumors; Orthodontic treatment